2008
DOI: 10.1242/jcs.024547
|View full text |Cite
|
Sign up to set email alerts
|

A non-apoptotic role for caspase-9 in muscle differentiation

Abstract: Caspases, a family of cysteine proteases most often investigated for their roles in apoptosis, have also been demonstrated to have functions that are vital for the efficient execution of cell differentiation. One such role that has been described is the requirement of caspase-3 for the differentiation of skeletal myoblasts into myotubes but, as yet, the mechanism leading to caspase-3 activation in this case remains elusive. Here, we demonstrate that caspase-9, an initiator caspase in the mitochondrial death pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 41 publications
9
123
3
1
Order By: Relevance
“…It was observed that depletion of caspase-9 or overexpression of Bcl-xL reduced caspase-3 activation and this had a limiting effect on the differentiation of myoblasts. 88 Osteogenic differentiation of mesenchymal stem cells involves caspase-3 activity, and caspase-3-deficient mice exhibit attenuated differentiation of the bone marrow stromal stem cells and consequently decreased bone mineral density. 89 It is noteworthy that the process of normal osteoblast differentiation requires the transient and potent activation of other caspases, including caspase-8 and -2, without any increase in osteoblast apoptotic cell death.…”
Section: Caspases In Cell-fate Determination and Differentiationmentioning
confidence: 99%
“…It was observed that depletion of caspase-9 or overexpression of Bcl-xL reduced caspase-3 activation and this had a limiting effect on the differentiation of myoblasts. 88 Osteogenic differentiation of mesenchymal stem cells involves caspase-3 activity, and caspase-3-deficient mice exhibit attenuated differentiation of the bone marrow stromal stem cells and consequently decreased bone mineral density. 89 It is noteworthy that the process of normal osteoblast differentiation requires the transient and potent activation of other caspases, including caspase-8 and -2, without any increase in osteoblast apoptotic cell death.…”
Section: Caspases In Cell-fate Determination and Differentiationmentioning
confidence: 99%
“…In addition, Dronc RNAi is able to further increase ectopic neuroblasts in numb S52F mutant, indicating that Dronc-Numb interaction is normally involved in regulating neuroblast homeostasis. Accumulating evidence suggests that caspases, in addition to their pro-apoptotic functions, also participate in other developmental process without inducing cell death (Geisbrecht and Montell, 2004;Huh et al, 2004a;Huh et al, 2004b;Kuranaga et al, 2006;Kuranaga and Miura, 2007;Maelfait and Beyaert, 2008;Murray et al, 2008). For example, Dronc has been implicated in a non-autonomous role in compensatory proliferation (Huh et al, 2004a;Wells et al, 2006).…”
Section: Research Articlementioning
confidence: 99%
“…Several studies have examined the signal cascades that activate and modulate caspase 3 during non-death responses, yet a definitive control mechanism has not been elucidated. [37][38][39] Such inactivation could indirectly end CAD activity by discontinuing proteolysis of ICAD. Intact ICAD (both long and short isoforms) can disassemble the CAD dimer, moreover our observation that ICAD-L is only partial cleaved (with a large pool of intact ICAD-L remaining) suggests that this mechanism maybe operative to prevent extensive DNA fragmentation.…”
Section: Curbing the Caspase3/cad Signalmentioning
confidence: 99%